2015
DOI: 10.1108/ijlma-03-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Bank competition and efficiency: empirical evidence from Indian market

Abstract: Purpose – The study aims to investigate the relationship between competition and efficiency. Using bank-level data for Indian banks, relationship between competition and efficiency is examined by applying the Granger causality test for the period 1996 to 2011. Design/methodology/approach – Lerner Index is a measure of market power and is applied for estimation of competition. Data envelopment analysis technique is applied for measuring efficiency in the Indian banking system along with the Granger causali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 33 publications
0
35
3
1
Order By: Relevance
“…The heightened of competition should encourage banks to reduce operating costs and, hence, eliminate inefficiencies in the banking industry (Turan, 2015). Arrawatia, Misra, & Dawar (2014) also found that competition positively effects efficiency and vice-versa. Then it needs to be examined whether the Islamic bank in ASEAN is efficient enough to face the tightening competition.…”
Section: Introductionmentioning
confidence: 99%
“…The heightened of competition should encourage banks to reduce operating costs and, hence, eliminate inefficiencies in the banking industry (Turan, 2015). Arrawatia, Misra, & Dawar (2014) also found that competition positively effects efficiency and vice-versa. Then it needs to be examined whether the Islamic bank in ASEAN is efficient enough to face the tightening competition.…”
Section: Introductionmentioning
confidence: 99%
“…Granger causality test investigates whether competition (C) results in efficiency (E) :( C  E) or efficiency results in competition (E  C) or both influence each other (C E). Granger Causality is denoted as follows (Arrawatia, et al, 2014):…”
Section: Resultsmentioning
confidence: 99%
“…Or the study of [10] uses data enveloping method (DEA) to measure the technical efficiency of banks in countries of Vietnam, Thailand, Malaysia, Philippines, Indonesia 1998 -2004. [11] use the DEA approach to estimate the effectiveness of the Indian banking system.…”
Section: Technical Efficiency Of Commercial Banksmentioning
confidence: 99%